External auditory canal cholesteatoma: staging and treatment strategies - He, Guanwen; Lin, Chang; Zhu, Zhongshou; Liu, Liangfeng; Wei, Rifu; Hong, Yiyun (Frontiers in Neurology, 2024)
ObjectiveTo investigate clinical staging systems and appropriate treatment strategies for external auditory canal cholesteatoma (EACC).MethodsWe performed comparative analysis of the features of several staging schemes (Holt, Naim, Shin, Chang, Kaneda, Hn, and He) of EACC; retrospective analysis of the clinical data of 44 patients with primary EACC, and analyzed the prognosis.ResultsHe’s staging system (2019) was found to be particularly clear and practical. It defines each lesion stage comprehensively, reflecting the disease’s progressive nature. According to He’s staging, 2 stage I lesions underwent transcanal cholesteatoma removal (TCR). For 28 stage II lesions, TCR was performed, with 12 cases additionally undergoing canalplasty. Among the 10 stage IIIA lesions, 2 were managed through outpatient debridement, while the remaining 8 underwent TCR combined with partial mastoidectomy and canalplasty (including 2 cases with reconstruction). Three stage IIIC lesions underwent canalplasty and tympanoplasty following partial mastoidectomy. In one case of stage IV lesion, treatment involved mastoidectomy, canalplasty, and abscessectomy. Recurrence occurred in three patients with stage II lesions treated with TCR alone, while the remainder showed no recurrence. One stage IIIA lesion who underwent outpatient debridement only was unable achieve a completely dry ear, and another stage IIIC lesion whose perforated tympanic membrane did not heal due to a fungal infection.ConclusionClinicians can refer to He’s staging for the clinical staging of EACC to devise appropriate treatment strategies; minimally invasive surgical procedures can be flexibly chosen depending on the extent of lesion involvement, under the premise of complete resection of the lesion, but regular follow-up is crucial.